Handbook of high field dynamic nuclear polarization - Michaelis, Vladimir K.; Griffin, Robert G.; Corzilius, Björn (Professor of physical chemistry); Vega, Shimon (eMagRes books., 2020)
This comprehensive handbook is a compendium of the current state-of-the art of high field Dynamic Nuclear Polarizationu2014from long-proven, early developments, up to todayu2019s hot topics. It covers all the relevant subjects that have made a direct or indirect contribution toward advancing this field, and focuses on topics such as: the theory behind the effects seen within DNP; instrumentation required for carrying out DNP; and specific applications of DNP including protein monitoring, catalysis, nanoparticles, biological and clinical studies. Development and application of techniques that have indirectly contributed to advancing MAS DNP NMR, such as DNP experiments on static solids within microwave resonant structures, and high-field EPR, are also examined. Handbook of High Field Dynamic Nuclear Polarization is presented in three sectionsu2014Theoretical Aspects, DNP Development (instrumentation / radical / sample), and DNP NMR Applications. The first section offers chapters on; solid and cross effect DNP; thermal mixing; Overhauser; and dissolution DNP. The second looks at: microwave technology, gyrotron, and IOE; homebuilt and commercial DNP spectrometers; and glassing vs. solvent-free DNP. The final section provides information on; amyloid, membrane, and nanocrystalline proteins; metals, and surface enhanced DNP; pharmaceuticals; nanoparticles; and much more.